De-gendering gendered occupations : analysing professional discourse - McDowell, Joanne (London : Routledge, 2021)
De-Gendering Gendered Occupations brings together contributions from researchers on language and gender studies and workplace discourse to unpack and challenge hegemonic gendered norms encoded in what are traditionally considered female occupations. The volume integrates a range of theoretical frameworks, including conversation analysis, pragmatics, and interactional sociolinguistics, to analyse data from such professions as primary education, healthcare, and speech and language therapy across various geographic contexts. Through this lens, the first part of the book examines men's linguistic practices with the second part offering a comparative analysis of 'male' and 'female' discourse. The settings discussed here allow readers to gain insights into the ways in which cultural, professional, and gendered identity intersect for practitioners in these professions and in turn, future implications for discourse around gendered professions more generally. This book will be key reading for students and researchers in sociolinguistics, discourse analysis, gender studies, cultural studies, and professional discourse.
OCLC-licensed vendor bibliographic record.
Keywords: Sexual division of labor; Professional employees -- Language; Sexism in communication; Communication in organizations; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics